Preliminary investigation on entrepreneurial intentions of young Malaysian accounting professionals - Jainurin Justine @ Abdul Aziz; Mohd Allif Anwar Abu Bakar; Nur Shahida Ab Fatah; Lee, Andy Chen Hiung (Penerbit UMS, 2021)
At the end of June 2021, the Malaysian Institute of Accountants (MIA) has 37,444 members. One of the MIA’s strategic objectives is to “promote the value proposition of accountancy profession and continuously uplift global recognition” with a target to grow its membership to 60,000 members by the year 2030. Accounting practitioners can contribute in achieving the membership target of MIA by starting a business and consequently creating accounting job opportunities. This preliminary research investigates the entrepreneurial intentions among Malaysian accounting practitioners below the age of 40 years. A survey was carried out online among 45 accounting professionals. While most respondents showed strong attitude and general intention towards running their own business, they indicated obstacles in the matter. The research findings can be used by relevant stakeholders to encourage accounting professionals to create businesses in the future. Suggestions for future research conclude the paper.